An Analysis of The Persistence of Wage Differentials in Malaysia - Ali , Malissa; Hamid, Zarinah; Idris, Zera Zuryana; Ahmad Hakim, Shabir; Zainudin , Dolhadi (International Journal of Economics, Management and Accounting, 2025)
Studies on the labor market wage gap have been published across nations with different variables of interest because inequality in labor compensation is a severe socioeconomic problem. Income inequality is studied through the wage gap Blinder-Oaxaca Decomposition method to investigate the contributing factors to the wage differential. As per previous studies, the factors were classified into endowments, coefficients, and interaction parts. Endowments capture the disparity in productivity or observable characteristics that may define the wage gap, the coefficient part is the wage structure built from discrimination or unobservable characteristics, and interaction is the component of how the other two interact with each other. Our study uses data from the Household Income Survey (HIS) conducted by the Department of Statistics Malaysia (DOSM) in 2022, 2019, and 2016. The total sample size is 35,884 observations (of which 12,735 are for the year 2022; 11,698 for 2019; and 11,451 for 2016). Findings show that the wage difference between Bumiputera and non-Bumiputera was reduced from 2016 to 2019. It increased again in 2022, however, higher than in 2016. The three-year mean for endowment effects is 39.55% of the wage difference and 60.45% for coefficient and interaction parts combined. Therefore, it is statistically evident that Bumiputera labor is compensated lower than non-Bumiputera. This study gives recent insights on the ethnic wage differentials with more updated datasets and identifies the determinants of wage differential which would help policymakers to tackle the root causes.